RETRACTED: Quality of Life and PTSD Symptoms, and Temperament and Coping With Stress - Burnos, Agnieszka; Bargiel-Matusiewicz, Kamilla M. (Frontiers in Psychology, 2018)
Due to advances in medicine a malignant neoplasm is a chronic disease that can be treated for a lot of patients for many years. It may lead to profound changes in everyday life and may induce fear of life. The ability to adjust to a new situation may depend on temperamental traits and stress coping strategies. The research presented in this paper explores the relationships between quality of life, PTSD symptoms, temperamental traits and stress coping in a sample of patients diagnosed with cancer. One hundred and twenty nine participants aged 24-81 years, 69 females diagnosed with breast cancer and 60 males diagnosed with lung cancer completed Formal Characteristics of Behaviour – Temperament Inventory (FCB-TI), Coping Inventory for Stressful Situations (CISS), PTSD Inventory (PTSD-C) and Quality of life SF-36 questionnaire. Higher level of emotional reactivity and higher level of perseveration was associated with lower emotional quality of life. Higher level of emotion oriented-coping and higher level of avoidant-distracted coping was associated with higher level of PTSD symptoms. Emotion-oriented coping and avoidant-distracted coping are ineffective in dealing with stress in the case of patients diagnosed with cancer, because they are associated with a higher level of PTSD symptoms. The significance of temperamental traits for quality of life in the situation of the patients is marginal. Control of specific factors concerned with current health and treatment status is needed the future research.